A Statistical Explanation of the Dunning–Kruger Effect - Magnus, Jan R.; Peresetsky, Anatoly A. (Frontiers in Psychology, 2022)
An explanation of the Dunning–Kruger effect is provided which does not require any psychological explanation, because it is derived as a statistical artifact. This is achieved by specifying a simple statistical model which explicitly takes the (random) boundary constraints into account. The model fits the data almost perfectly. JEL Classification A22; C24; C91; D84; D91; I21